Ketertarikan Berbagai Spesies Serangga pada Pan Trap di Lahan Kacang Panjang (Vigna sinensis L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Yanti, Pari; Prasetyo, Julia Cassandra; Zahra, Melia; Nurjannah, Nurjannah; Apriani, Regina; Anggreni, Uus Amelia; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Yanti P, Prasetyo CP, Zahra M, Nurjannah N, Apriani R, Anggreni UA, Umayah A, Gunawan B, Arsi A. 2022. The preference of various insect species in pan trap in long bean field (Vigna sinensis L.) in Ogan Ilir Regency, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 524-532. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Long bean (Vigna sinensis) is a vegetable crop that is often attacked by various species of insect pests, causing a decrease in the quality and quantity of plants that cause economic losses for farmers. This paper aimed to determine the interest of insect species to color preference as an alternative control of insect pests. Observations were carried out on long bean plantations in three villages, namely Tanjung Seteko, Tanjung Pering, and Permata Baru villages located in Ogan Ilir Regency, South Sumatra by using purposive sampling with 3 replications observed after 12 hours of installing pan traps which were red, yellow, green, and blue in the field. From research conducted on long bean fields in Ogan Ilir Regency, several orders of insects were obtained, namely the orders Coleoptera, Diptera, Hemiptera, Hymenoptera, Lepidoptera, Collembola, Orthoptera, and Thysanoptera. The total number of individual insects obtained in all trays in the field amounted to 1.005 insects. The level of insect species diversity on long bean plantations in Tanjung Seteko, Tanjung Pering, and Permata Baru villages were medium, low, and low, respectively. Insect species found in the long bean plantations are more attracted to the yellow tray. Among the four colors of the tray, insect species are more attracted to the yellow tray because the yellow color resembles the color of their food. The use of a yellow pan trap can be one on the insect pest control in long bean fields and can be a tool in monitoring insects in the field.